The relationship of the formation of dental fear between mothers and their 7 to 9 year-old children - Cheema, Jasmine Kaur; Gartika, Meirina; Herdiyati, Yetty (Faculty of Dentistry Universitas Padjadjaran, 2022)
Introduction: Dental fear is a common occurrence that responds to the stress induced by various dental procedures. Its intensity varies from nervousness and anxiety to dental phobia, and it is considered the main barrier to successful completion of treatment. This research aims to analyse the relationship of the formation of dental fear between mother and their 7 to 9-year-old children. Methods: The research design was analytical studies with a cross-sectional survey technique, with samples chosen by the simple random sampling method. Thirty-five mothers and children aged 7-9 years who attended Neglasari 2 and Neglasari 5 Public Elementary School, Sadang Serang, Bandung, were the respondents. This study used a questionnaire called the Dental Subscale of the Children's Fear Survey Schedule (CFSS-DS), tested and proven to be a reliable and valid psychometric instrument for dental fear evaluation in children in Bahasa Indonesia. This study was analysed using Spearman's rank correlation coefficient. Results: The mean score of the mothers was 24.314, and the mean score of the children was 23.571. The correlation value was 0.765. The figure scales in the 'strong' criteria. Conclusion: There is a strong relationship between the formation of dental fear in mothers and their 7-9 years-old children.